Healthcare-associated infections and antimicrobial resistance in severe acquired brain injury: a retrospective multicenter study - Castellani, Giovanna Barbara; Maietti, Elisa; Leonardi, Gloria; Bertoletti, Erik; Trapani, Filippo; Battistini, Alberto; Tedeschi, Sara; Piperno, Roberto; Viale, Pierluigi (Frontiers in Neurology, 2023)
Background Recent studies underscore that healthcare-associated infections (HAIs) and multidrug-resistant (MDR) HAIs affect rehabilitation outcomes and hospital length of stay (LOS) for severe acquired brain injury (sABI). Objective This study aimed to estimate HAI incidence in different sABI rehabilitation settings and determine risk factors and HAI impact on neuromotor and cognitive recovery. Methods We conducted a retrospective multicenter study in two semi-intensive units (SICUs), two high-specialty post-acute units (PAUs), and one long-term care (LTC) rehabilitation facility. Data extraction was performed by experienced clinicians, using a structured Excel file and they agreed upon criteria for case definitions of healthcare. The main outcome measures were the HAI and MDR HAI incidence and the LOS, the functional recovery was measured using the Level of Cognitive Functioning and Disability Rating Scale. Results There were 134 sABI participants. The calculation of the probability level was adjusted for three pairwise comparisons among settings (0.05/3 = 0.017). The HAI and MDR HAI incidences were significantly higher in SICU (3.7 and 1.3 per 100 person-days) than in other settings (LTC: 1.9, p = 0.034 and 0.5, p = 0.026; PAU: 1.2, p < 0.001 and 0.3, p < 0.001). HAI and MDR HAI risk variables included older age, an increased number of devices, and carbapenemase-producing Enterobacteriaceae (CPE) colonization, while a high prealbumin plasma value seemed to have a protective effect. Conclusion HAIs are related to longer LOS, and colonization is associated with poor prognosis and poor functional outcomes with reduced ability to achieve the cognitive capacity of self-care, employability, and independent living. The need to ensure the protection of non-colonized patients, especially those with severe disabilities on admission, is highlighted.